Extreme Air Pollution Conditions Adversely Affect Blood Pressure and Insulin Resistance: The Air Pollution and Cardiometabolic Disease Study. Issue 1 (January 2016) - Brook, Robert D.; Sun, Zhichao; Brook, Jeffrey R.; Zhao, Xiaoyi; Ruan, Yanping; Yan, Jianhua; Mukherjee, Bhramar; Rao, Xiaoquan; Duan, Fengkui; Sun, Lixian; Liang, Ruijuan; Lian, Hui; et al.
Abstract : Mounting evidence supports that fine particulate matter adversely affects cardiometabolic diseases particularly in susceptible individuals; however, health effects induced by the extreme concentrations within megacities in Asia are not well described. We enrolled 65 nonsmoking adults with metabolic syndrome and insulin resistance in the Beijing metropolitan area into a panel study of 4 repeated visits across 4 seasons since 2012. Daily ambient fine particulate matter and personal black carbon levels ranged from 9.0 to 552.5 µg/m 3 and 0.2 to 24.5 µg/m 3, respectively, with extreme levels observed during January 2013. Cumulative fine particulate matter exposure windows across the prior 1 to 7 days were significantly associated with systolic blood pressure elevations ranging from 2.0 (95% confidence interval, 0.3–3.7) to 2.7 (0.6–4.8) mm Hg per SD increase (67.2 µg/m 3 ), whereas cumulative black carbon exposure during the previous 2 to 5 days were significantly associated with ranges in elevations in diastolic blood pressure from 1.3 (0.0–2.5) to 1.7 (0.3–3.2) mm Hg per SD increase (3.6 µg/m 3 ). Both black carbon and fine particulate matter were significantly associated with worsening insulin resistance (0.18 [0.01–0.36] and 0.22 [0.04–0.39] unit increase per SD increase of personal-level black carbon and 0.18 [0.02–0.34] and 0.22 [0.08–0.36] unit increase per SD increase of ambient fine particulate matter on lag days 4 and 5). These results provide important global public health warnings that air pollution may pose a risk to cardiometabolic health even at the extremely high concentrations faced by billions of people in the developing world today. Abstract : Supplemental Digital Content is available in the text.